INTRODUCTION TO THE SECTORAL EFFECTS AND OPERATING MECHANISM OF MONETARY TRANSMISSION IN INDIA. - Kumar, Praveen; Ranawat, Mahendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Given the complexity and sophistication of India's economy, especially, the efficiency of monetary transmission in the country has drawn greats interest. Under this study, a sectoral analysis is conducted to understand how changes in monetary policy affect many spheres of the economy. This analysis also underlines the variations in gearbox systems. The intensity of financial inclusion, intensity of dependency on formal credit, and intensity of which each sector is linked with the whole economy describe few structural variables that characterize the degree of sensitivity of some sectors variation in policy. For sectors like manufacturing and services, that are based on credit, for instance, show more sensitivity monetary actions than usually self-financed companies like agriculture. Moreover, underscored by the research is the relevance of institutional and commercial factors in determining the dissemination of policy. Many factors play important roles:effectiveness of financial intermediation; the consistency of interest rates; and the interval of time separating policy execution from its consequences.